Big Data, Machine Learning, Artificial Intelligence and Blockchain in Corporate Governance - Meiryani, Meiryani; Warganegara Dezie Leonarda; Andini, Vidhiya (Foresight and STI Governance, 2023)
The paper analyses the dynamics of scientific research in, and practical application of key Industry 4.0 technologies in corporate governance, namely big data, artificial intelligence, machine learning, and blockchain. The contribution of specific authors, citation, and collaboration networks are assessed, along with that of individual countries and research organisations. A bibliometric network analysis of publications indexed in the Scopus and OpenAlex databases for 2011–2022 revealed a steady increase in the number of publications on the topic under consideration, and therefore a growing interest in it. The use of the abovementioned technologies in corporate governance is expected to lead to increased performance and transparency, and improved cybersecurity. The authors provide recommendations for various groups of users to maximise the potential of Industry 4.0 technologies for businesses, and the overall economy.